The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.52547/jommid.10.3.114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterizations and Antimicrobial Susceptibility of Extended-Spectrum ß-lactamase (ESBL) Producing Proteus spp. Clinical Isolates in Babol, Northern Iran

Abstract: Introduction: Proteus spp. are opportunistic members of Enterobacteriaceae, accounting for 10% of urinary tract infections and other primary clinical infections. They produce extended-spectrum beta-lactamases (ESBL) that can confer resistance to beta-lactam antibiotics. This study aimed to investigate the prevalence, antimicrobial susceptibility, molecular characteristics, and genetic relationship of ESBL-producing Proteus spp. clinical isolates in Babol, Northern Iran. Methods: In this cross-sectional study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…ESBLs are becoming more prevalent [27]. In [28], reported that blaTEM and blaSHV genes prevalence rates were 60% and 23.3%, respectively. The result of PCR analysis of this study referred to the presence of a single band (861bp) of the target sequence of the blaTEM gene of P. mirabilis and P. vulgaris isolates, except PM8, PM19 and PV32 isolates, as shown in Figures 6 and 7.…”
Section: Resultsmentioning
confidence: 99%
“…ESBLs are becoming more prevalent [27]. In [28], reported that blaTEM and blaSHV genes prevalence rates were 60% and 23.3%, respectively. The result of PCR analysis of this study referred to the presence of a single band (861bp) of the target sequence of the blaTEM gene of P. mirabilis and P. vulgaris isolates, except PM8, PM19 and PV32 isolates, as shown in Figures 6 and 7.…”
Section: Resultsmentioning
confidence: 99%